Why Do People Save in Cash? Distrust, Memories of Banking Crises, Weak Institutions and Dollarization - Helmut Stix (Oesterreichische Nationalbank (OeNB), 2012)
The paper analyzes why households in transition economies prefer to hold sizeable shares of their assets in cash at home rather than in banks. Using survey data from ten Central, Eastern and Southeastern European countries, I document the relevance of this behavior and show that cash preferences cannot be fully explained by whether people are banked or unbanked. The analysis reveals that a lack of trust in banks, memories of past banking crises and weak tax enforcement are important factors. Moreover, cash preferences are stronger in dollarized economies where a "safe" foreign currency serves as a store of value.
Keywords: E41; O16; G11; D12; P34; 330; Cash demand; cash hoarding; household finance; trust in banks; social capital; dollarization; Geld; Sparen; Privater Haushalt; Währungssubstitution; Bankenkrise; Lernprozess; Vertrauen; Wirtschaftsordnung; Transformationsstaaten